Pelatihan Deteksi Dini Konflik Sosial dan Keagamaan pada Masa Pemilu di Kabupaten Kerinci dan Kota Sungai Penuh: Training on Early Detection of Social and Religious Conflicts During the Election Period in Kerinci District and Sungai Penuh City - S., M. Nurzen; Hadi, Al Amin; Candra, Hadi; Wafi, Mahmud Hibatul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The early detection of conflict is a crucial process in conflict prevention to avoid more complex situations in society. Politically competitive activities have the potential to trigger social division and broader conflicts. This community service initiative aims to provide concrete solutions for religious-social conflicts resulting from the political process. The initiative is implemented through training and mentoring for members of the Election Supervisory Board (Bawaslu) in Kerinci District and Sungai Penuh City, involving relevant stakeholders such as the National Unity and Politics Agency (Kesbangpol), Regional Police (Polres), and the Forum for Interfaith Harmony (FKUB). Participants in the training displayed high enthusiasm by actively participating in Q&A sessions, group discussions, presentations, and providing reflections. Qualitatively, the training has positively impacted participants’ insights, attitudes, and skills in analyzing and detecting conflicts in society. Participants gained in-depth knowledge of the concept of early conflict detection and methods to identify potential conflicts before reaching higher levels of escalation. In terms of attitude, the training was effective in shaping a positive mindset and sensitivity to conflict issues, reinforcing peace values, and encouraging participants to adopt a proactive approach to conflict prevention efforts. Finally, through case studies and simulations, participants acquired the necessary skills to identify early signs of conflict and develop appropriate handling strategies.